The water knife - Bacigalupi, Paolo (Alfred A. Knopf, 2015)
"The American Southwest has been decimated by drought. Nevada and Arizona skirmish over dwindling shares of the Colorado River, while California watches, deciding if it should just take the whole river all for itself. Into the fray steps Las Vegas water knife Angel Velasquez. Detective, assassin, and spy, Angel "cuts" water for the Southern Nevada Water Authority and it's boss, Catherine Case, ensuring that her lush, luxurious arcology developments can boom in the desert and that anyone who challenges her is left in the gutted-suburban dust."